Shrinking Violet: Media Role in Identity Construction in Stephen Chbosky’s The Perks Of Being A Wallflower - Aninda Pradita (Universitas Pendidikan Indonesia (UPI), 2013)
The present study entitled Shrinking Violet: Media Role in Identity Construction in Stephen Chbosky’s The Perks of Being a Wallflower focuses on the issue of identity construction and media role on the main character of the story. The study investigates the main character’s, Charlie, identity construction in the novel and the contribution of media role, particularly print-rich environment, in the construction of Charlie’s identity. The study is conducted within a descriptive text analysis by applying a qualitative method and is framed by theoretical frameworks such as identity theory (Hall, 2000) and young adult literature (Nilsen Donelson, 2001). The results demonstrate that Charlie’s identity is constructed through two different contexts: ‘home and family’ context and ‘school and friends’ context. The study also finds that there are roles of print-rich environment play to the construction of Charlie’s identity: as a tool of literacy and critical thinking improvement as well as a bibliotherapy.Keywords: Identity Construction, Young Adult, Media, Print-rich environment, Bibliotherapy.